Mater et Magistra: Peran Penting dalam Membangun Kesadaran Sosial Umat Katolik - Marike Amanda; Theresia Noiman Derung (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2025)
This research analyzes the role of the Mater et Magistra encyclical in building social awareness among Catholics. Using a qualitative method with a literature study approach, this research examines encyclical documents, books, articles, and related official Church documents. The main focus of the research is the principles contained in Mater et Magistra, such as human dignity, general welfare, justice and solidarity, as well as their relevance to modern social issues. The results show that Mater et Magistra was not only relevant in its time, but also provides concrete guidance to deal with current social challenges, such as poverty, economic injustice, and human rights violations. The encyclical encourages Catholics to actively engage in social activities, advocate for just policies, and establish programs that support the welfare of society. Thus, Mater et Magistra remains an important reference in promoting the values of social justice and solidarity in a global society. The encyclical is not only an ethical guide, but also an effective educational tool to inspire Catholics to face social change and become agents of change in their communities.